The Banchero-Braschi of The fox from up above and the fox from down below, by Jose Maria Arguedas. Source to understand a secular cult - Hernández Lefranc, Harold (2019)
The present text has as objective to do an anthropological lecture of a character in principle of fiction, Braschi, of the last novel, unfinished, by Jose Maria Arguedas (†1969), The fox from up above and the fox from down below (1971), but that is sustained, in the vision of the novelist, in a real character, Luis Banchero Rossi (†1972), distinguished peruvian businessman of the fish industry. The character that Arguedas conceives and draws, since his liberating political presupposed, it is a execration that attempts against nature and humanity, against life and morality; it is the evil encarnate, a falsifier, a liberator feigned; finally, a caricature of the Che Guevara –representation that contrasts paradoxically with the mystified reading that some populars sectors in Lima do in the present when they visit the Banchero’s tomb and they ask him miracles and favors like to a saint.